Respuestas

2012-11-06T22:58:02+01:00

3x - 4y=-6  +

2x + 4y=16

________

5x      =10

x=10/5

x=2

 

reemplazando en la primera ecuacion

 

3(2)- 4y=-6

6-4y=-6

6+6=4y

12/4=y

3=y

 

2012-11-06T23:44:09+01:00

Igualación:

3x - 4y = -6

2x +4y = 16\left \{ {{x=\frac{+4y -6}{3}} \atop {x= \frac{-4 +16}{2}}} \right

 4y - 6 = -4y + 16 4y + 4y = 16+6 8y = 22 y = \frac{22}{8} .

3x - 4( \frac{22}{8} ) = -6

3x -  \frac{32}{8} = -6

24x - 32 = -48

24x= -48 + 32

24x= - 16

x= \frac{- 16}{24}